Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1002/pbc.27604
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric oncology and stem cell transplant patients with healthcare‐associated Clostridium difficile infection were already colonized on admission

Abstract: Clostridium difficile is the leading cause of healthcare‐associated infections worldwide. The diagnosis of C. difficile infection (CDI) in pediatric oncology patients is complex as diarrhea is common, and there is a high rate of colonization in infants and young children. This study was conducted to assess the accuracy of the surveillance definitions of healthcare‐associated CDI (HA‐CDI) and to determine the prevalence of toxigenic C. difficile colonization among pediatric oncology and stem cell transplant pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…The increased risk in recipients with a history of prior CDI may reflect increased C difficile colonization or absence of antibodies to the toxin. One study found that asymptomatic colonization with a toxigenic strain of C difficile on admission was predictive of subsequent CDI in pediatric oncology recipients, and almost all the isolates shared identical pulsed‐field gel electrophoresis patterns with the initial colonizing isolate . A retrospective study examining C difficile prophylaxis with oral vancomycin in adult allo‐HCT recipients found no cases of CDI in the 90 recipients who received prophylaxis while 20% of recipients who did not receive prophylaxis developed CDI .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased risk in recipients with a history of prior CDI may reflect increased C difficile colonization or absence of antibodies to the toxin. One study found that asymptomatic colonization with a toxigenic strain of C difficile on admission was predictive of subsequent CDI in pediatric oncology recipients, and almost all the isolates shared identical pulsed‐field gel electrophoresis patterns with the initial colonizing isolate . A retrospective study examining C difficile prophylaxis with oral vancomycin in adult allo‐HCT recipients found no cases of CDI in the 90 recipients who received prophylaxis while 20% of recipients who did not receive prophylaxis developed CDI .…”
Section: Discussionmentioning
confidence: 99%
“…One study found that asymptomatic colonization with a toxigenic strain of C difficile on admission was predictive of subsequent CDI in pediatric oncology recipients, and almost all the isolates shared identical pulsed-field gel electrophoresis patterns with the initial colonizing isolate. 32 A retrospective study examining C difficile prophylaxis with oral vancomycin in adult allo-HCT recipients found no cases of CDI in the 90 recipients who received prophylaxis while 20% of recipients who did not receive prophylaxis developed CDI. 33 Additional studies are needed before recommendations for screening and prevention strategies can be made for recipients with a history of CDI before transplant.…”
Section: Ta B L Ementioning
confidence: 99%
“…Because of the ubiquity of C. difficile spores in the environment, focusing on ways to increase the resilience of the host to colonization is one important prevention strategy. However, modulation of host factors that influence virulence of C. difficile already present in the gut is also a key aspect of prevention, as CDI is often caused by C. difficile that is already residing in the gut before the onset of symptomatic CDI rather than acquisition of a new infection (3) .…”
Section: Discussionmentioning
confidence: 99%
“…As discussed above, a fiber-deficient diet has been shown to hinder clearance of C. difficile after challenge (15) . This is particularly relevant in a clinical context as recent studies of both pediatric and adult oncology patients have shown asymptomatic colonization rates with C. difficile of ∼30% and ∼10%, respectively (3, 31) . Further, in pediatric patients it was demonstrated that the vast majority of “hospital-acquired” CDI may be caused by a strain of C. difficile that is present at admission rather than a strain acquired during the patient stay (3) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation